What health professionals should know about the health effects of air pollution and climate change on children and pregnant mothers - Poursafa, Parinaz (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Health professionals face the adverse health effects of climate change and air pollution in their practices. This review underscores the effects of these environmental factors on maternal and children's health, as the most vulnerable groups to climate change and air pollution. METHODS: We reviewed electronic databases for a search of the literature to find relevant studies published in English from 1990 to 2011. RESULTS: Environmental factors, notably climate change and air pollution influence children's health before conception and continue during pregnancy, childhood, and adolescence. Experts have suggested that such health hazards may represent the greatest public health challenge that humanity has faced. The accumulation of greenhouse gases such as carbon dioxide, primarily from burning fossil fuels, results in warming which has an impact on air pollution particularly on levels of ozone and particulates. Heat-related health effects include increased rates of pregnancy complications, pre-eclampsia, eclampsia, low birth weight, renal effects, vector-borne diseases as malaria and dengue, increased diarrheal and respiratory disease, food insecurity, decreased quality of foods (notably grains), malnutrition, water scarcity, exposures to toxic chemicals, worsened poverty, natural disasters and population displacement. Air pollution has many adverse health effects for mothers and children. In addition to short-term effects like premature labour, intrauterine growth retardation, neonatal and infant mortality rate, malignancies (notably leukaemia and Hodgkin lymphoma), respiratory diseases, allergic disorders and anaemia, exposure to criteria air pollutants from early life might be associated with increase in stress oxidative, inflammation and endothelial dysfunction which in turn might have long-term effects on chronic non-communicable diseases. CONCLUSIONS: Health professionals have an exclusive capability to help prevent and reduce the harmful effects of environmental factors for high-risk groups, and should consider this capacity in their usual practice.